A t10-based method for evaluation of ore pre-weakening and energy reduction. (August 2015) - Zuo, Weiran; Shi, Fengnian
Highlights: A t 10 -based method for evaluation of ore pre-weakening effect is developed. A single parameter ( CAb ) is used to represent the percentage change of A  ∗  b . The method can predict energy reduction due to the pre-weakening effect. Abstract: Currently the effect of the pre-weakening of ore particles by high voltage pulses is evaluated by the percentage change of A  ∗  b values between pulse-treated and untreated ore particles. The values of A  ∗  b, widely used as an ore breakage competence indicator in the mineral industry, are determined from the parameters of the JKMRC breakage models. In this study a t 10 -based method was developed to predict the degree of size reduction, t 10, of pulse-treated particles from that of untreated particles broken at the same size/energy level. This method incorporates one parameter, CAb, which is equivalent to the percentage change of A  ∗  b values. The t 10 -based method was validated using nine sets of comparative JK Rotary Breakage Tester data on pulse-treated and untreated ore samples over a wide range of impact specific energies and particle sizes. The t 10 -based method can be used to calculate the energy reduction due to the pre-weakening effect in the downstream comminution process. It indicates that the energy reduction by pre-weakening increases with an increase in the target product fineness and the degree of pre-weakening, and with the decrease in feed particle size.